A cross-sectional study on the telemedicine usage and glycemic status of diabetic patients during the COVID-19 pandemic (Faculty of Medicine Universitas Indonesia, 2021)
BACKGROUND The coronavirus disease 2019 (COVID-19) pandemic disrupts selfmanagement in diabetic patients in Indonesia. This study aimed to determine the telemedicine usage and factors contributing to glycemic control in type 2 diabetes mellitus (T2DM) patients during the pandemic. METHODS A cross-sectional study was conducted in T2DM patients aged 25–54 years. The questionnaire included general characteristics, diabetes conditions, consultation factors, and self-care management. Glycemic status was evaluated using glycated hemoglobin (HbA1c) levels, which was categorized into poor (HbA1c≥7%) and good glycemic control (HbA1c<7%). Data were analyzed using chi-square and binary logistic regression. RESULTS Of 264 patients, only 19.2% used telemedicine and 60.2% had poor glycemic control during the pandemic. Overweight or obesity (odds ratio [OR] = 5.740 [95% confidence interval [CI] = 2.554–12.899]; p<0.001), insulin injection (OR = 3.083 [95% CI = 1.238–7.677]; p = 0.016), and frequent fried food consumption (OR = 5.204 [95% CI = 1.631–16.606]; p = 0.005) were the factors contributing to poor glycemic control. The risk is lower if exercised regularly (OR = 0.036 [95% CI = 0.007–0.195]; p<0.001) and consulted with a doctor using telemedicine (OR = 0.193 [95% CI = 0.044–0.846]; p = 0.029) or in-person visits (OR = 0.065 [95% CI = 0.016–0.260]; p<0.001). CONCLUSIONS Glycemic control was not optimal during the COVID-19 pandemic. Therefore, keeping a healthy lifestyle and staying connected with a doctor are important to ensure optimal blood glucose control and reduce the risk of diabetesrelated complications.